What was the China’s spatial-temporal evolution characteristics of cross-sensitivity of ecosystem service value under land use transition? A case study of the Jiangjin, Chongqing - Zhang, Chuanhua; Tan, Hongmei; Zhou, Miao; Wang, Zhongshu (Frontiers in Environmental Science, 2022)
Exploring the sensitivity of ecosystem service value (ESV) under land use transformation (LUT) is helpful to promote the rational use of regional land, improve the regional ecological environment carrying capacity, and realize the sustainable development of human beings. Using land use data of Jiangjin Chongqing from 2009 to 2019, this study measured the effect of ecological service value under land use transition in Jiangjin, and analyzed the spatiotemporal evolution characteristics of ecosystem service value based on the land use transfer matrix, change contribution rate (ESVab) and Coefficient of im-proved cross-sensitivity (CICS). The results showed that (a) the total ESV increased year by year in Jiangjin; (b) the ESV change of woodland was the largest, followed by water bodies and cultivated land; (c) taking the Yangtze River as the boundary, the ESV in the south was higher than that in the north, but the ESV in the north and south of the Yangtze River increased to different degrees; (d) taking the Yangtze River as the boundary, the ESV in the south of the Yangtze River was higher than that in the north, but the ESV in the north and south of the Yangtze River was increasing at different degrees; (e) the contribution rate of forest land was the largest, the contribution rate of cultivated land and woodland was highly correlated with topography and slope, and the contribution rate of water bodies had no obvious spatial distribution characteristics; (f) the CICS between cultivated land, woodland and other land types was higher, and the conversion between cultivated land, woodland and other land types was mainly in the medium-high ecological sensitive areas, while the conversion between water bodies, built-up land and other land types was mainly in the medium-low ecological sensitive areas; and (g) the highly ecologically sensitive areas of the conversion between unused land and other land types were mainly distributed in the southern mountainous area of Jiangjin. It aims to provide important guidance for solving the contradiction between humanity and land and regional environmental problems, so as to realize the sustainable development of the region and environment.